Rok 1812 w poezji rosyjskiej - Andrzej Ksenicz (In Gremium. Studies in History, Culture and Politics, 2014)
The Year 1812 in Russian PoetryNapoleon’s invasion of Russia in 1812 had a great impact throughout Russian society and was also reflected in Russian literature. The poets of the period, both those widely remembered today as well as those forgotten, were the group of artists who most immediately responded to the event. Memories of those days of the challenge were indelibly printed on the Russian mind. National poets such as A. Puszkin and M. Lermontow reached back to 1812 and depicted the Russian peoples’ heroic commitment to the defense of their country.